AB0803 Celiac Disease and Positive IGA Tissue Transglutaminase in Patients with Distal Radius or Ankle Fracture: Interim Analysis. (10th June 2014) - Hjelle, A.M.; Mielnik, P.; Apalset, E.; Tell, G.S.
Abstract : Background: Patients with celiac disease (CD) have low mineral bone density [1]. Evidence of increased fracture risk in CD patients is conflicting. Studies are heterogeneous and difficult to compare, however overall findings indicate an increased risk of fracture [2]. Objectives: To investigate whether patients with CD or positive IgA tissue transglutaminase (TTG) are at increased risk of distal radius or ankle fracture compared to healthy age- and sex matched controls. Methods: Patients over the age of 40 with acute distal radius or ankle fracture and controls with no fracture are included in this case control study. Bone mineral density (BMD) of the hips and spine is measured, history of previous fracture, comorbidities, medication, physical activity, smoking habits, body mass index and nutritional factors are registered. Serum analysis including TTG is performed. In order to get sufficient statistical power we estimated a priori that 400 patients and 200 controls were needed. Results: After including 134 patients with fracture, four (3.0%) had previously diagnosed CD, and seven (5.2%) had TTG, a combined total of 8.2%. Among 94 controls, one had CD and two positive TTG, a total of 3.2%. This difference is not statistically significant. The patients had significantly lower BMD than controls (T-score (+SD) L1-L4 -1.407±0.249, controls -0.358±0.287, and T-score of total hip -1.461±0.174, controls -0.649±0.242). Patients with fracture had a longer history of smoking (p=0.014), and a higher proportion were current smokers (p=0.046). Conclusions: Interim analyses indicate that adult patients over the age of 40 with fracture of the distal radius or ankle may have å greater risk of CD or positive TTG. Although the proportion of CD or positive TTG were more than twice that in controls, the differences were not statistically significant. We are continuing accruing patients, and updated analyses will be presented. References: Bianchi, M.L. and M.T. Bardella, Bone in celiac disease. Osteoporos Int, 2008. 19(12): p. 1705-16. Olmos, M., et al., Systematic review and meta-analysis of observational studies on the prevalence of fractures in coeliac disease. Dig Liver Dis, 2008. 40(1): p. 46-53. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1238